Two-dimensional organic-inorganic heterostructures of in situ-grown layered COF on Ti3C2 MXene nanosheets for lithium-sulfur batteries. (December 2020) - Meng, Ruijin; Deng, Qiyi; Peng, Chengxin; Chen, Bingjie; Liao, Kexuan; Li, Lunjin; Yang, Ziyi; Yang, Donglei; Zheng, Lei; Zhang, Chi; Yang, Jinhu
Graphical abstract: The constructed CTF/TNS heterostructures show superior Li-S battery performance as a sulfur host due to their multiple-in-one advantages of 3D spatial sulfur confinement, dual-site chemical polysulfides anchoring and efficient electron/ion transport. Highlights: 2D heterostructures of layered CTF in situ-grown on Ti3C2 nanosheets were fabricated. Covalent Ti-N interaction between TNS and CTF components enabled a stable interface. The 2D heterostructures held multiple-in-one advantages for superior Li-S batteries. Li-S batteries based on the 2D heterostructures showed outstanding cycling stability. Abstract: The development of sulfur host materials with simultaneous suppressed shuttle effect, improved electrical/ionic conductivity and high sulfur loading is highly desired for lithium-sulfur batteries. Herein, we proposed that two-dimensional heterostructures made of layered covalent triazine framework on Ti3 C2 MXene nanosheets (CTF/TNS) as a sulfur host show multiple-in-one advantages for lithium-sulfur batteries. The integrity of organic CTF with ordered pore structure and inorganic TNSs with high conductivity imparts the heterostructures three-dimensional spatial confinement for high sulfur loading and efficient electron/ion transport for improved reaction kinetics. In addition, lithiophilic N sites in CTF and sulfurophilic Ti sites in TNSs enable dual-site chemical anchoring of polysulfides to effectively suppress shuttle effect. With a high sulfur loading of 76 wt%, the S@CTF/TNS cathode shows high reversible capacity (1441 mA h g −1 at 0.2 C), outstanding cycling stability (up to 1000 cycles at 1 C with a 0.014 % capacity decay rate per cycle) and excellent rate capability. Notably, even with a high areal sulfur loading of 5.6 mg cm −2, a high capacity retention of 94 % is still obtained after 100 cycles.